Intraspecific variations in Indian isolates of Bipolaris sorokiniana infecting wheat based on morphological, pathogenic and molecular characters - and P. SRINIVAS, RASHMI AGGARWAL*, V.B. SINGH, M.S. GURJAR, SANGEETA GUPTA (Indian Phytopathology, 2009)
High variability in 103 isolates of wheat pathogen Bipolaris sorokiniana, collected from different geographical zones of India, was observed based on their morphological characters, pathogenicity and DNA fingerprinting. Based on their colony characteristics the isolates were categorized into five groups. The frequency of the dull white/greenish black colony type was maximum (38.83%), while both black, suppressed type and white fluffy type colonies showed minimum frequency (11.65%) in the population studied. A total of 40 isolates from five identified groups were further studied for growth rate, sporulation, pathogenic and molecular variability. Colony diameter after seven days of incubation ranged from 20.3 mm (BS-95) to 63 mm (BS-63). Highest spore production was observed in BS-69 (10x107 /colony) and lowest in BS-95 (1.0x107 / colony). Isolate BS-48 remained non sporulative even after15 days of incubation. Although all the isolates were pathogenic but their pathogenicity on susceptible genotype, Agra local varied. Isolate BS-49 showed average disease index (ADI) value of 4.5 while isolate BS-75 exhibited highest ADI of 63.4. Based on the disease response on differential hosts, five pathotypes were identified. Pathotype 1 constituted maximum isolates and was least virulent while pathotype 5 isolates were highly virulent as they produced S/HS response on most of the differential hosts. No correlation between groups identified based on colony characteristics and pathogenicity was observed. RAPD analysis of isolates of these 40 isolates showed 100% polymorphism. The amplified DNA band ranged between 200 bp to 3.5 Kb. The dendrogram generated based on polymorphic data revealed a considerable amount of diversity among the isolates, grouping them in ten clusters. Primer OPB 18 specifically amplified a DNA band of 260bp in isolate BS-53 collected from Malan (HP), which could be used as a specific marker to identify strain differences.